The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fimmu.2020.565484
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Endotoxin Exposure Induces Fetal and Neonatal Renal Inflammation via Innate and Th1 Immune Activation in Preterm Pigs

Abstract: Chorioamnionitis (CA) predisposes to preterm birth and affects the fetal mucosal surfaces (i.e., gut, lungs, and skin) via intra-amniotic (IA) inflammation, thereby accentuating the proinflammatory status in newborn preterm infants. It is not known if CA may affect more distant organs, such as the kidneys, before and after preterm birth. Using preterm pigs as a model for preterm infants, we investigated the impact of CA on fetal and neonatal renal status and underlying mechanisms. Fetal pigs received an IA dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
2
14
1
Order By: Relevance
“…Annotated proteins were further sorted into the effect and exposure protein groups. Compared with the data obtained in our previous study (Muk et al, 2020), the CSF proteome had partial overlap with the corresponding plasma proteome (44.3% overlap of total annotated proteins), indicating that (i) at least some of the identi ed CSF proteins were produced locally in the brain and (ii) CSF protein composition underwent time-dependent dynamic changes.…”
Section: Prenatal Lps Exposure Marginally Alters the Csf Protein Pro Le At Birthcontrasting
confidence: 68%
See 1 more Smart Citation
“…Annotated proteins were further sorted into the effect and exposure protein groups. Compared with the data obtained in our previous study (Muk et al, 2020), the CSF proteome had partial overlap with the corresponding plasma proteome (44.3% overlap of total annotated proteins), indicating that (i) at least some of the identi ed CSF proteins were produced locally in the brain and (ii) CSF protein composition underwent time-dependent dynamic changes.…”
Section: Prenatal Lps Exposure Marginally Alters the Csf Protein Pro Le At Birthcontrasting
confidence: 68%
“…Brie y, 54 fetuses from three pregnant sows (Large White × Danish Landrace × Duroc) were randomly allocated to receive an intra-amniotic injection of either 1 mg LPS/fetus (Escherichia coli, serotype 055:B5; Sigma-Aldrich, Copenhagen, Denmark) or control (saline or no injection; CON) at 103 days of gestation (E103). After 3 days, at E106, which corresponds to 90% gestation (full-term birth is 117 ± 2 days), the fetuses were delivered by cesarean section and randomly allocated either to be sacri ced shortly after delivery at Day 1 (P1; CON n = 14, LPS n = 16) or reared for 5 days (P5; n = 12 for each group) as previously described (Muk et al, 2020). The changes in systemic in ammatory marker levels and blood cell counts were previously published (Nguyen et al, 2018).…”
Section: Animal Experimentation and Tissue Collectionmentioning
confidence: 99%
“…At 19 days, male pigs had slightly lower hemoglobin and haematocrit values than females, potentially related to diminished erythropoiesis by the smaller kidneys ( 74 ), but more studies are required to verify sex effects on renal structure and function. This organ could be particularly susceptible to perinatal stressors, as indicated by our recent studies on fetal inflammation on gut, lung, liver, immunity and kidney development in preterm pigs ( 33 , 57 , 75 77 ). In the literature on production pigs, males do not consistently show reduced neonatal survival and growth ( 18 20 , 30 ), hence sex-specific survival, growth and adaptation may be most pronounced for immature newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated global alterations in both innate and adaptive immune cell populations in preterm rats 79,80 and pigs [81][82][83] . Recently a preterm pig model exposed to endotoxin demonstrated immune activation in the kidney 84 . In that study, Lyz1 expression in the kidney was higher in the preterm group as compared to the term group.…”
Section: Discussionmentioning
confidence: 99%